Risk variables of external apical root resorption during orthodontic treatment - Barroso,Maria Carolina Feio (2012)
INTRODUCTION: External apical root resorption (EARR) is an adverse outcome of the orthodontic treatment. So far, no single or associated factor has been identified as responsible for EARR due to tooth movement. OBJECTIVE: This study investigated the association of risk variables (age, gender, extraction for orthodontic treatment and Angle classification) with EARR and orthodontic treatment. METHOD: The sample (n=72) was divided into two groups according to presence (n=32) or absence (n=40) of EARR in maxillary central and lateral incisors after orthodontic treatment. RESULTS: There were no statistically significant differences in EARR according to age, gender, extraction or type of malocclusion (p>0.05). CONCLUSION: The risk variables examined were not associated with EARR in the study population.